Genetic Diversity and Genome-Wide Association Study of Morphological and Quality Traits in Peach Using Two Spanish Peach Germplasm Collections - Mas-Gómez, Jorge; Cantín, Celia M.; Moreno, María Ángeles; Martínez-García, Pedro J. (Frontiers in Plant Science, 2022)
Peach (Prunus persica (L.) Batsch) is one of the most important stone fruits species in terms of world production. Spanish peach production is currently the second largest in the world and the available cultivars in Spain includes a great source of genetic diversity with variability in fruit quality traits and postharvest disorders tolerance. In order to explore the genetic diversity and SNP-trait associations in the Spanish germplasm,the new peach 18K SNP v2 array was used to genotype 287 accessions belonging to the two National Peach Germplasm Collections placed at the Agrifood Research and Technology Centre of Aragon (CITA) and at the Experimental Station of Aula Dei (EEAD)-CSIC. The high density of the new SNP array allowed to identify 30 groups of synonymies, which had not been identified before using low-density markers. In addition, new findings of genomic rearrangements of ‘Starcrest’, a sport of ‘Springcrest’, were detected showing a possible chromosome replacement of a 13.5 Mb region. Previous suggestions about Spanish diversification regions agreed with our genetic diversity and LD decay results using high-density markers. A Genome-Wide Association Study (GWAS) detected 34 significant SNP-trait association with the type of leaf glands (TLG), fruit hairiness, and fruit texture. The impact of the significant SNPs was studied with SnpEff. Affected genes encode several important family proteins involved in trichome formation and powdery mildew resistance (linked to TLG in peach). The genetic distance among cultivars obtained, together with SNP-trait associations found, provide new knowledge for marker-assisted selection and crossing approaches in peach breeding programs.